Propriedades de pasta e térmicas de misturas instantâneas de farinha de soja, fécula e farelo de mandioca - Trombini, Fernanda Rossi Moretti [UNESP]; Leonel, Magali [UNESP] (EIA Energy in Agriculture, 2010)
The application of extrusion technology in the food industry has enabled the development of new commercial products of fast preparation, and maintaining the nutritional characteristics after the process. During this process there are changes in raw material due to the action of temperature, humidity and mechanical friction resulting in a modified product which can be used in various industrial applications. This work aimed to evaluate the effect of the composition of the raw material and operating conditions of the extrusion process on the properties of paste and thermal properties in the development of a functional instant flour of cassava and soybean. The results showed significant effects of all operating parameters on the rheological properties studied. The extruded flours showed no residual gelatinization enthalpy, suggesting that the starch in the samples was gelatinized. The experimental conditions of the smallest percentages of cassava residue (10%) and high soybean flour (25%) mixed with cassava starch, extrusion temperature of 75ºC and low screw speed (170rpm) leads to obtain instant flour with desirable characteristics.

A aplicação da tecnologia de extrusão na indústria alimentícia tem possibilitado a elaboração de novos produtos comerciais de rápido preparo, e que mantêm as características nutricionais após o processo. Durante o processo tecnológico, a matéria-prima sofre modificações devido às ações da temperatura, umidade e fricção mecânica resultando em um produto modificado para aplicações em alimentos. Neste trabalho objetivou-se avaliar o efeito da composição da matéria-prima e das condições operacionais do processo de extrusão sobre as propriedades de pasta e térmicas na produção de uma farinha instantânea funcional de mandioca e soja. Os resultados obtidos mostraram efeitos significativos de todos os parâmetros operacionais sobre as propriedades reológicas estudadas. As farinhas extrusadas não mostraram entalpia de gelatinização residual, sugerindo que todo o amido presente nas amostras foi gelatinizado. As condições de menores porcentagens de farelo de mandioca (10%), maiores de farinha de soja (25%) misturados a fécula de mandioca, temperatura de 75ºC e rotação da rosca (190rpm) permitiram a obtenção de farinha instantânea com propriedades térmicas e de pasta desejadas para farinhas instantâneas de uso alimentar.
Paste and thermal properties of instant mixtures of soybean flour, cassava starch and fibrous residue
Keywords: Extrusion; Cassava; Viscosity; Extrusão; Amido; Viscosidade